Braingate: Developing a Device to Provide Motor Impaired Patients with a Novel Neural Output - Serruya, M.D.; Wagenen, R.A. Van; Guillory, S.; Caplan, A.H.; Saleh, M.; Donoghue, J.P.; Morris, Dan; Hatt, B.W. (Society for Neuroscience Abstracts, 33th Annual Meeting of the Society for Neuroscience, 2003, 2003)
An implanted neural interface system may eventually afford patients with severe motor impairment a new output signal from their central nervous systems. By deriving output signals directly from the cerebral cortex, the BrainGate Neural Interface may provide a signal that can function in patients with a broad range of motor impairments. Previous studies in non-human primates (Serruya et al., 2002 Nature 416:141) indicate that the neural activity of a small number of cortical neurons coupled to simple mathematical decoding algorithms can generate a behaviorally useful output signal. The system consists of an intracortical microelectrode array, an amplifier and signal conditioning system (processor module), a decoder and a patient computer interface. The sensor is based on the Cyberkinetics 100 channel silicon electrode array and is designed to be implanted into the cortex. In its current version the array is connected externally through a 100-contact percutaneous connector. This implant has been tested in non-human primates. Signal processing involves standard spike discrimination. The decoder is designed to build mathematical relations between desired actions and brain output. A clinical trial protocol has been developed and initial sites for clinical trials are being explored. The protocol includes measures designed to characterize the safety profile of this new device, and measures to assess the ability of patients to use the novel output to drive a variety of computer programs including assistive software and standard desktop interfaces.